Implementation of demand-oriented ventilation with adjustable fan network. Issue 4 (April 2020) - Wang, Huan; Wang, Guijin; Li, Xianting
Airflow patterns are essential for heating, ventilation and air conditioning (HVAC) systems. Traditional HVAC systems are predesigned and operated using a fixed airflow pattern. However, the indoor occupancy and heat source always vary and therefore, the fixed flow pattern cannot efficiently maintain the required indoor environment conditions. In this study, a novel Adjustable Fan Network (AFN) for improving airflow pattern manoeuvrability is proposed. It integrates multiple small and adjustable axial fans into an AFN, enabling it to change the airflow pattern based on the actual demand with only one set of equipment. Further, the outflow characteristics of two types of axial fans were measured using a quad-view colour sequence particle streak velocimetry (CSPSV) in a test chamber. The ventilation system was then designed based on typical scenarios. Finally, the performance of the AFN was evaluated under different scenarios using a quad-view CSPSV. Based on the results, it was evident that the AFN can provide a better direct supply of air to the occupied zone under different scenarios. With the growing demand for personal thermal comfort and energy-saving in HVAC systems, the novel AFN system has a great potential to be a highly controllable terminal for demand-oriented ventilation.